Choice Behavior in Transition: Development of Preference With Ratio and Interval Schedules - Mazur, J.E. (Journal of Experimental Psychology: Animal Behavior Processes, 1992)
In Experiment 1, the choice responses of 8 pigeons were observed during 50 periods of transition. Each condition began with equal probabilities of reinforcement on 2 response keys and switched to unequal probabilities. With the ratio of the 2 probabilities held constant, preference for the higher probability developed more rapidly when the 2 probabilities were high than when they were low. In Experiment 2, each condition began with 2 equal variable-interval schedules, but later 1 key delivered 60%, 75%, or 90% of the reinforcers. The rate of approach to asymptotic performance was roughly the same with all 3 reinforcement percentages. These and previous results pose difficulties for some well-known models of acquisition, but the results are well described by a simple model that states that the strength of each response is independently increased by reinforcement and decreased by nonreinforcement.
Keywords: Animal; Attention; Choice Behavior; Color Perception; Motivation; Orientation; Pigeons; Probability Learning; Problem Solving; Reinforcement Schedule; Support, U.S. Gov't, P.H.S.; animal; article; attention; color vision; decision making; dept.psy; learning; motivation; orientation; pigeon; problem solving; reinforcement